You Were Better Than Expected–An Experimental Study to Examine Expectation Change in a Non-clinical Sample - Groth, Rosa-Marie; Rief, Winfried (Frontiers in Psychology, 2022)
Background Reduced sensitivity to rewards as well as the tendency to maintain dysfunctional expectations despite expectation-disconfirming evidence (cognitive immunization) are considered core features of various mental disorders. It is therefore important for clinical research to have paradigms that are suitable to study these phenomena. We developed a new experimental paradigm to study explicit expectation change after prior expectation induction and violation. Its validity is tested by applying the paradigm to healthy individuals. Materials and Methods In the main part of the study (experiment 1) we examined whether it is possible to change healthy individuals’ (Sample size 56) task-specific and generalized performance expectations through expectation-disconfirming experiences. We used a high-difficulty performance task to induce initially negative expectations regarding participants’ ability to successfully work on that unknown task. In the second part of the study, the difficulty of the test was lowered in one experimental condition, in order to disconfirm the negative expectations of the first part, while the other group continued with high test difficulty to confirm the negative expectations. We measured the participant’s explicit performance expectations before and after completing the tests. In experiment 2 (Sample size 57), we investigated the impact of different test instructions on expectation change. Using the same paradigm as in experiment 1, we added an “immunization-inhibiting” manipulation for one group and an “immunization-enhancing” manipulation for the other group. Results In experiment 1, we were able to show that individuals changed their expectations according to variations of task difficulty. Adding instructions to manipulate cognitive immunization inhibited expectation change regardless of condition (experiment 2). Conclusion Our approach allowed us to examine the effects of implicitly acquired performance expectations on explicit, verbalized expectation change. The new experimental paradigm used in this study is suitable to induce performance expectations, and to examine expectation-change among healthy individuals (experiment 1). Instructions to enhance or inhibit cognitive immunization processes both inhibited expectation change (experiment 2). The results are discussed within the context of current models of expectation change, cognitive immunization, and reward sensitivity.